Dampak E-Government dalam Meningkatkan Efisiensi dan Efektivitas Tata Kelola Pemerintahan - Muhammad Jafar AW (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to analyze the impact of e-government implementation on increasing efficiency and effectiveness in governance. This is because the important role of digital technology has contributed to improving the public administration process and decision-making in government entities. Digitalization has provided convenience and speed in administrative governance which has an impact on improving public services. Data collection techniques through in-depth interviews and observations of civil servants in Serang Regency. This study found that the implementation of e-government has a significant impact on increasing efficiency in data management and public services, as well as the effectiveness of governance. Digitalization in the context of governance also has a significant impact on efforts to strengthen public services and transparency in the government sector. This study also found that strengthening digital infrastructure and training of human resources in the public sector is needed to maximize the implementation of e-government in governance.